Utilization of zakāt through entrepreneurship programs - Ariyani, Diyah; Rahmayanti, Dini (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
The potential of zakāt for the economic empowerment of people who have an entrepreneurial spirit will be realized if the distribution is productive. This productive zakāt will positively impact alleviating poverty, increasing income, and giving birth to new entrepreneurs. This study analyses matters relating to the distribution and utilization of zakāt funds at Rumah Zakat Semarang through entrepreneurship programs and their empowerment management. The method used in this study is qualitative research with Rumah Zakat Semarang as the research object. Data were obtained through interviews and documentation, then analyzed by the descriptive analysis method. The results showed that the distribution of productive zakāt funds at the Rumah Zakat Semarang in the entrepreneurship program was distributed through economic empowerment (Senyum Mandiri), namely community empowerment oriented to integrated community empowerment. This empowerment uses the Integrated Community Development (ICD) model as an integrated and sustainable community-based concept. The results of this study can be used as evaluation and input for zakāt institutions in empowering the community’s economy through productive zakāt funds.